Synthesis of optimal heat and mass exchange networks using a two-step hybrid approach including detailed unit designs - Short, Michael (Department of Chemical Engineering, 2017)
This PhD thesis develops a methodology for the synthesis of optimal heat and mass exchanger networks through a novel hybrid method. The two-step procedure makes use of simplified exchanger models in a network optimisation step, followed by a detailed design where the exchangers found in the network synthesis step are modelled in detail. Subsequent iterations of the network design step are then updated with information from the detailed network designs. The algorithm has certain advantages over previous methods in that the network optimisation is based on more realistic representations of the actual units therein and also that the method increases the likelihood of attaining a globally optimal solution through the generation and assessment of multiple candidate networks throughout the algorithm. The method can be used in a variety of applications and is demonstrated to be effective for large problems and multi-period scenarios. The thesis also shows that the method can be used in conjunction with multiple individual unit optimisation techniques including heuristics and fully explicit optimisation methods.